2016
DOI: 10.5414/cn108584
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio and platelet-tolymphocyte ratio in evaluation of inflammation in end-stage renal disease

Abstract: Our findings in a cohort of ESRD patients on maintenance HD revealed higher values for NLR and PLR in patients with higher levels of inflammation along with a significant positive correlation of both NLR and PLR with hs-CRP levels. Being a simple, relatively inexpensive and universally available method, whether or not calculation of NLR and PLR offers a plausible strategy in the evaluation of inflammation in ESRD patients in the clinical practice should be addressed in larger scale randomized and controlled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 0 publications
8
83
5
5
Order By: Relevance
“…Malhotra et al [24] suggested that NLR could serve as a potential surrogate marker for CRP in hemodialysis patients. Similarly, Ahbap et al [6] found that NLR was significantly positively correlated with hsCRP levels in patients with ESRD on maintenance hemodialysis. In patients on prevalent hemodialysis, NLR was also associated with all-cause mortality [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malhotra et al [24] suggested that NLR could serve as a potential surrogate marker for CRP in hemodialysis patients. Similarly, Ahbap et al [6] found that NLR was significantly positively correlated with hsCRP levels in patients with ESRD on maintenance hemodialysis. In patients on prevalent hemodialysis, NLR was also associated with all-cause mortality [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NLR has been recognized as a novel inflammatory marker for assessing cardiovascular disease severity and poor prognosis in the general population [4] and in patients with ESRD [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, this research did not find a correlation between the CRP level and the parameters calculated. In a recent study, Ahbap et al [32] found that hemodialysis had a significant relationship to the NLR, PLR, and CRP in end-stage renal disease (ESRD) patients on maintenance hemodialysis. Similarly, they reported that the relationship was too small to draw a conclusion that the NLR and PLR were good substitutes for CRP in ESRD patients on maintenance hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Subsequently higher values in NLR and PLR have been linked to greater inflammatory status and worse prognosis among patients with various disease conditions including cardiovascular disease, 17 chronic obstructive pulmonary disease, 18 liver cirrhosis, 19 and CKD. 20 Furthermore, recent studies have indicated that NLR and PLR were associated with inflammation and may predict mortality among hemodialysis patients as well, 2126 but their small study sample sizes make it difficult to draw a definite conclusion regarding their detailed associations with mortality and comparative usefulness in mortality-predictability when compared to other clinically accessible markers related to CKD. To address this knowledge gap, we studied a 5-year large national cohort of incident hemodialysis patients in the United States and investigated the relationship of NLR and PLR with all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%